Extinction Distributions in Nearby Star-resolved Galaxies. I. M31 - Yuxi Wang; Jian Gao; Yi Ren; Bingqiu Chen (The Astronomical Journal)
An extinction distribution of the Andromeda galaxy (M31) is constructed with member stars as tracers by fitting multiband photometric data from UKIRT/WFCAM, Panoramic Survey Telescope and Rapid Response System 1, and Gaia DR3. The resulting extinction distribution covers approximately 10 deg ^2 of M31 with a resolution of approximately 50″, providing the largest coverage to date based on stellar observations. The derived average extinction, A _V = 1.17 mag, agrees well with previous studies. To account for foreground extinction, an extinction map of the Milky Way toward M31 with a resolution of ∼1 $\mathop{.}\limits^{{\rm{^{′} }}}$ 7 is also constructed, yielding an average extinction of A _V ≈ 0.185 mag. The results offer a valuable tool for extinction correction in future observations, such as those from the China Space Station Telescope, and provide insights for improving dust models based on the spatial distribution of dust in galaxies like M31.